The Use of the Literacy Tree Media in Improving Early Childhood Literacy Skills - Melisa Agustina; Retnoningsih Retnoningsih; Syahru Ramadhan (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study was motivated by the low ability of early childhood students to recognize letters at Darmawan Early Childhood Education Center, where most children still have difficulty distinguishing the shapes and sounds of letters. This condition is caused by conventional learning activities that do not utilize interesting learning media. Therefore, this study aims to determine the effectiveness of using Literacy Tree media in improving early childhood students' ability to recognize letters. This study uses a qualitative approach with a descriptive research type. The research data sources include teachers, students, and observations of learning activities in the classroom. Data collection techniques were carried out through observation, interviews, and documentation. Meanwhile, the data analysis technique used the Miles and Huberman interactive analysis model, which includes the stages of data reduction, data presentation, and conclusion drawing. The results showed that there were several forms of application carried out by Darmawan PAUD teachers, namely the creation and arrangement of literacy tree media in the classroom environment, letter recognition activities through literacy tree media, vocabulary development and early reading skills, storytelling and language expression activities for children through literacy trees, exploration of student understanding through letter leaf sticking activities, and elaboration of student understanding in letter and word guessing activities. The implementation has shown results, with the Literacy Tree media significantly improving children's ability to recognize letters. Before implementation, only about 37-40% of children were able to recognize letters, but after the activities, this increased to 87-90%. Children became more active, enthusiastic, and confident in naming and recognizing letters through fun activities such as sticking letter leaves, storytelling, and word guessing